STRATEGI PEMASARAN, SITUASI PERSAINGAN, DAN PERMODALAN DALAM MEMPENGARUHI KINERJA UKM PENGRAJIN TERASI KAWASAN PESISIR KOTA LANGSA - Dhian Rosalina (Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the effect of marketing strategies, competitive situations, and capital on the performance of shrimp paste SMEs in the coastal area of ​​Langsa City. The number of respondents in this study was twenty-four shrimp paste in the coastal area of ​​Langsa City in two villages: Lhokbani and Simpang Lhee which are craftsmen centers for shrimp paste / rebon shrimp paste in Langsa City. The sampling technique used is non probablity sampling. The analytical method used is multiple linear regression analysis. The results of this study are 1) Marketing strategies do not have a significant impact on business performance, 2) The competitive situation does not have a significant impact on business performance, and 3) capital has a positive and significant effect. From the results of the analysis it was found that this research was consistent with previous research that the problem of capital was still a serious obstacle for small and medium businesses in Indonesia. DOI : https://doi.org/10.26905/jbm.v6i2.3262